2016
DOI: 10.1002/14651858.cd002124.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplements for dysmenorrhoea

Abstract: This review is published as a Cochrane Review in the Cochrane Database of Systematic Reviews 2016, Issue 3. Cochrane Reviews are regularly updated as new evidence emerges and in response to comments and criticisms, and the Cochrane Database of Systematic Reviews should be consulted for the most recent version of the Review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 42 publications
0
61
1
4
Order By: Relevance
“…Single randomized controlled trials showed the effect of vitamin supplements on the reduction of menstrual pain reduction [63,66,67], but a Cochrane meta-analysis on the effect of dietary supplements for primary dysmenorrhea lacked high quality evidence to support the effectiveness and safety of any dietary supplement for dysmenorrhea. Therefore, more research with higher methodological qualities are required [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Single randomized controlled trials showed the effect of vitamin supplements on the reduction of menstrual pain reduction [63,66,67], but a Cochrane meta-analysis on the effect of dietary supplements for primary dysmenorrhea lacked high quality evidence to support the effectiveness and safety of any dietary supplement for dysmenorrhea. Therefore, more research with higher methodological qualities are required [24].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, case reports, letters to the editor, and review articles were excluded. Trial studies on dietary supplements and herbal drugs were excluded because of the presence of a recent published systematic review on this topic [24].…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, many patients with PD turn to alternative therapies, such as acupuncture, moxibustion, or herbal medicine [9]. …”
Section: Discussionmentioning
confidence: 99%
“…15 Highdose vitamin D supple mentation has shown some promise in a randomised controlled trial and could be tried alongside other approaches. 16 The evi dence on spine manipulation and herbal medicine remains inconclusive due to poorquality data and therefore these treat ments cannot be recommended.…”
Section: ■ Prescribing In Practicementioning
confidence: 99%